Beyond the Metropolis: Drivers of Online Food Delivery Adoption - Ikhwan Arief; Armijal Armijal; Ridhamelia Ridhamelia (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2025)
This study investigates the determinants of purchase intention for Online Food Delivery (OFD) services among Generation Z and Millennial consumers in a non-metropolitan city within an emerging market, using ShopeeFood in Padang, Indonesia, as a case study. The rapid saturation of OFD services necessitates a re-evaluation of classical technology adoption models. This research employs an extended Technology Acceptance Model (TAM) framework, integrating digital marketing as a key antecedent. Utilizing a quantitative survey methodology with a sample of 102 consumers, the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Perceived Usefulness (B=0.584, p<0.001) and Digital Marketing (B=0.262, p<0.05) are significant positive predictors of Purchase Intention. Critically, Perceived Ease of Use (B=0.046, p<0.05) was found to have no significant effect. The model collectively explains 56.1% of the variance (R2) in purchase intention, demonstrating substantial predictive power. This study's principal contribution lies in providing empirical evidence that in a maturing digital service market, ease of use may transition from a direct driver of intention to a baseline 'hygiene factor'. Consequently, the core utility of the service and the effectiveness of strategic marketing efforts significantly influence consumer choice. These findings offer crucial implications for OFD platforms seeking to capture market share in the next frontier of digital growth: the emerging economies' secondary and tertiary cities.